The Mediating Role of Psychological Flexibility and Emotional Flexibility in the Relationship Between Metacognitions and Emotional Schemas with Rumination - Eshghifar, Reyhaneh; Mohammadkhani , Shahram; Hasani, Jafar (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: The present study aimed to investigate the mediating role of psychological flexibility and emotional flexibility in the relationship between metacognitions and emotional schemas with rumination. Methodology: This research was done in the form of structural equation modeling (SEM). Participants were 578 people from the non-clinical population residents of Tehran who were selected by voluntary sampling method. Then they completed the Ruminative Response Scale, Positive Beliefs about Rumination Scale, Negative Beliefs about Rumination Scale, Emotion Schemas Scale - Persian version, Acceptance and Action Questionnaire II, Emotional Flexibility Scale.Findings: The results of the model evaluation indicated that metacognitions, emotional schemas, psychological flexibility and emotional flexibility directly have a significant effect on rumination. The mediating role of psychological flexibility and emotional flexibility was significant in the relationship between metacognitions and rumination. The mediating role of emotional flexibility in the relationship between emotional schemas and rumination was not significant, but the mediating role of emotional flexibility in the relationship between metacognitions and rumination was significant.Conclusion: Based on the findings of this study, modifying metacognitions along with increasing psychological flexibility and emotional flexibility, as well as modifying maladaptive emotional schemas along with increasing psychological flexibility, can be effective in creating preventive strategies and rumination management.